2004
DOI: 10.2458/azu_jrm_v57i5_mellado
|View full text |Cite
|
Sign up to set email alerts
|

Age and body condition score and diets of grazing goats

Abstract: Diet selection by juvenile and adult non -pregnant, non-lactating goats and the diets of adult non -productive goats with low (<1.5; grading scale 0-5) and moderate ( >_ 2.5) body condition score (BCS) are described by microhistological analysis of fecal samples for a Chihuahuan desert vegetation in northern Mexico. In the rainy season, adult goats utilized more (P < 0.10) shrubs than juvenile goats (70.4 vs 58.6 %), but, in the dry season, the diet of both groups contained equal amounts of shrubs. The proport… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

2
6
0

Year Published

2005
2005
2024
2024

Publication Types

Select...
4
1

Relationship

1
4

Authors

Journals

citations
Cited by 7 publications
(8 citation statements)
references
References 19 publications
2
6
0
Order By: Relevance
“…Grass was the least prevalent of the 3 forage classes in the goat diets, and although graminoids constituted an important part of goat diets, goats continued to follow a browsing strategy. Grass use by goats in our study was several times larger than that reported in shrub-dominated plant communities in arid zones (Sidahmed et al 1981;Mellado et al 1991Mellado et al , 2003Mellado et al , 2004, which reaffirms that goats are very flexible in the vegetation classes they consume. By looking at the selectivity indices, it was clear that grasses were not preferred items for goats.…”
Section: Discussionsupporting
confidence: 82%
See 1 more Smart Citation
“…Grass was the least prevalent of the 3 forage classes in the goat diets, and although graminoids constituted an important part of goat diets, goats continued to follow a browsing strategy. Grass use by goats in our study was several times larger than that reported in shrub-dominated plant communities in arid zones (Sidahmed et al 1981;Mellado et al 1991Mellado et al , 2003Mellado et al , 2004, which reaffirms that goats are very flexible in the vegetation classes they consume. By looking at the selectivity indices, it was clear that grasses were not preferred items for goats.…”
Section: Discussionsupporting
confidence: 82%
“…Two forbs of singular importance for the 3 animal species throughout the year were S. elaeagnifolium and S. angustifolia, which made up 9, 12 and 10% of the prairie dog, goat and sheep diets, respectively (average across 4 seasons). The importance of these forage species for prairie dogs (Fagerstone et al 1977;Summers and Linder 1978;Uresk 1984) and goats (Mellado et al 2003(Mellado et al , 2004 has been previously reported. The trends for forbs in diets of the 3 kinds of animals and standing crop suggest that competition was intense throughout the study period.…”
Section: Discussionmentioning
confidence: 91%
“…This finding agrees with the results of previous studies in this habitat (Mellado et al, 2003(Mellado et al, , 2004b. Solanum elaeagnifolium, a highly unpalatable forb (Mellado et al, 2008b), was preferred during the dry season (spring) by the goats in the control pasture.…”
Section: Forage Preferencesupporting
confidence: 94%
“…Forbs usually become important components of goat diets if the availability of high-quality forbs is increased, normally during the rainy season (Mellado et al, 2003(Mellado et al, , 2004b. In the present study, the goats selected a higher (p < 0.01) proportion of forbs during the fall (the end of the rainy season) than during other seasons.…”
Section: Botanical Composition Of Dietsmentioning
confidence: 75%
“…C. squarrosa is the main plant species in the experimental region, and was highly available to lambs; therefore it was a preferred diet component of lambs for both longer and shorter grazing times. Lambs/kids prefer to browse on fresh, young and palatable forages at pasture 14 , 15 . The high palatable and nutritional content of A. ramosum most likely accounted for it being strongly selected by lambs in July.…”
Section: Discussionmentioning
confidence: 99%